(untitled) (Journal of Bangladesh Academy of Sciences, 2012)
Polycrystalline Li-Cu mixed ferrites were prepared by double sintering ceramic technique. Cu substituted Li ferrites having the general formula Li0.5-x/2CuxFe2.5-x/2O4 where, x = 0.0 to 1.0 and the samples were sintered at 1100°C for 3 hours in the normal atmosphere. The prepared samples were confirmed in the spinel structure by the X-ray diffraction method. The lattice parameter and porosity were calculated for different compositions. The electrical resistivity and dielectric constant have been investigated as a function of composition and temperature. It was observed that the resistivity decreased with increasing temperature and exhibited semiconducting nature of the sample. The compositional variation of resistivity and dielectric constant showed inversed trend with each other at room temperature for Cu content, x > 0.3. This was found to support the electron hopping conduction mechanism. The dielectric constant increased slowly with temperature in the beginning and after that dielectric constant increased rapidly for different samples. As the temperature increased, thermal energy provided to the sample played an important role to decrease the relaxation time and hence there was an increase in dielectric constant. Dielectric constant has been observed as a function of frequency and it decreased with increasing frequency. Key words: Electrical resistivity; Porosity; Dielectric constant; Electron hopping DOI: http://dx.doi.org/10.3329/jbas.v35i2.9428 JBAS 2011; 35(2): 221-228